2011
DOI: 10.1002/chem.201100396
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Synthesis of Inhibitors of the Two First Enzymes of the Bacterial Heptose Biosynthetic Pathway: Towards Antivirulence Molecules Targeting Lipopolysaccharide Biosynthesis

Abstract: L-Heptoses (L-glycero-D-manno-heptopyranoses) are constituents of the inner core of lipolysaccharide (LPS), a molecule playing key roles in the mortality of many infectious diseases as well as in the virulence of many human pathogens. The inhibition of the first enzymes of the bacterial heptose biosynthetic pathway is an almost unexplored field to date although it appears to be a very novel way for the development of antivirulence drugs. We report the synthesis of a series of D-glycero-D-manno-heptopyranose 7-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 67 publications
0
33
0
Order By: Relevance
“…In 2013, Vincent and Tikad explored the DBCE reaction to perform the synthesis of conformationally constrained methyl 3,6‐anhydro‐ l ‐glycero‐α‐ d ‐manno‐heptopyranoside 7‐phosphate 106 , an analogue of methyl d ‐glycero‐ d ‐gluco‐heptopyranose 7‐phosphate 107 , which is the best inhibitor of both enzymes GmhA (IC 50 =34 μ m ) and HldE (IC 50 =9.4 μ m ), the two first enzymes of the bacterial heptose biosynthetic pathway (Scheme ) . Based on the debenzylative cyclization induced by DAST as a key step in this strategy, the target 3,6‐anhydroheptosides 103 – 105 were achieved after a few hours in good to excellent yields, whatever the nature of starting l ‐heptoside used ( 100 – 102 ; Scheme ).…”
Section: Activation Of Hydroxy Groups Positioned δ To a Benzyl Ethermentioning
confidence: 99%
“…In 2013, Vincent and Tikad explored the DBCE reaction to perform the synthesis of conformationally constrained methyl 3,6‐anhydro‐ l ‐glycero‐α‐ d ‐manno‐heptopyranoside 7‐phosphate 106 , an analogue of methyl d ‐glycero‐ d ‐gluco‐heptopyranose 7‐phosphate 107 , which is the best inhibitor of both enzymes GmhA (IC 50 =34 μ m ) and HldE (IC 50 =9.4 μ m ), the two first enzymes of the bacterial heptose biosynthetic pathway (Scheme ) . Based on the debenzylative cyclization induced by DAST as a key step in this strategy, the target 3,6‐anhydroheptosides 103 – 105 were achieved after a few hours in good to excellent yields, whatever the nature of starting l ‐heptoside used ( 100 – 102 ; Scheme ).…”
Section: Activation Of Hydroxy Groups Positioned δ To a Benzyl Ethermentioning
confidence: 99%
“…We found that the scaling-up of the latter step was highly problematic. Actually, we have recently reported a modification of the Fleming-Tamao procedure allowing the synthesis of l,d-heptoside 5 on a multigram scale, [26] this compound was thus selected as the starting material for the preparation of alkynylated heptoses 9 and 10 (Scheme 1).…”
Section: Synthesismentioning
confidence: 99%
“…The copper-catalyzed cycloaddition of azide 11 with alkyne 9 gave model compound A in 65 % yield. The synthesis of the targeted octoside building block 14 was performed from the known molecule 12 [26] (Scheme 2). Per- The preparation of fullerene sugar balls C 60 A C H T U N G T R E N N U N G (A-F) 12 is depicted in Scheme 3 and Scheme 4.…”
Section: Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the search for inhibitors of LPS biosynthesis has been a valuable strategy in antibacterial drug design. Syntheses of inhibitors of the biosynthetic pathways leading to KDO [17], to lipid A [18], and more recently, to L-glycero-D-manno-heptose [19] have been explored.…”
Section: Targeting the Cell Wall Biosynthesismentioning
confidence: 99%